Isolation and characterization of three benzylisoquinoline alkaloids from Thalictrum minus L. and their antibacterial activity against bovine mastitis. (4th December 2016) - Mushtaq, Saleem; Rather, Muzafar Ahmad; Qazi, Parvaiz H.; Aga, Mushtaq A.; Shah, Aabid Manzoor; Shah, Aiyatullah; Ali, Md. Niamat
Abstract: Ethno-pharmacological relevance: The roots of Thalictrum minus are traditionally used in the treatment of inflammation and infectious diseases such as bovine mastitis. However, there are no reports available in literature till date regarding the antibacterial studies of T. minus against bovine mastitis. Aim of the study: The present study was undertaken to evaluate the antibacterial potential of crude extract of T. minus (root) and some of its isolated constituents against bovine mastitis in order to scientifically validate its traditional use. Materials and methods: A total of three alkaloid compounds were isolated from the DCM: MeOH extract of roots of T. minus using silica gel column chromatography. Structural elucidation of the isolated compounds was done by using spectroscopic techniques like mass spectrometry and NMR spectroscopy. Pathogens were isolated from cases of bovine mastitis and identified by using 16S rRNA gene sequencing. The broth micro-dilution method was used to evaluate the antibacterial activities of DCM: MeOH extract and isolated compounds against mastitis pathogens. Results: The three isolated compounds were identified as benzylisoquinoline alkaloids(1) 5′-Hydroxythalidasine, (2) Thalrugosaminine and(3 ) O-Methylthalicberine. Compounds(2) and(3) are reported for the first time from the roots of T. minus. Five mastitis pathogens viz., Staphylococcus xylosus, Staphylococcus lentus, Staphylococcus equorum, Enterococcus faecalis and Pantoea agglomerans were identified on the basis of sequence analysis of isolates using the nucleotide BLAST algorithm. This study reports for the first time the isolation and molecular characterization of mastitis pathogens from Kashmir valley, India. The DCM: MeOH extract exhibited broad spectrum antibacterial activities that varied between the bacterial species (MIC=250–500 µg/ml). 5′-Hydroxythalidasine and Thalrugosaminine showed promising antibacterial activity with MIC values of 64–128 µg/ml while Staphylococcus species were found to be the most sensitive strains. Conclusions: The antibacterial activities of the DCM: MeOH extract and isolated compounds support the traditional use of T. minus in the treatment of bovine mastitis. Graphical abstract: